Treatment for pure red cell aplasia after major ABO‐incompatible allogeneic stem cell transplantation: a multicentre study. (12th April 2021) - Longval, Thomas; Galimard, Jacques‐Emmanuel; Leprêtre, Anne‐Claire; Suarez, Felipe; Amiranoff, Denise; Cazaux, Marine; Kaphan, Eleonore; Michonneau, David; Dhedin, Nathalie; Coman, Tereza; Nguyen Quoc, Stéphanie; Peffault de Latour, Régis; et al.
Summary: Pure red cell aplasia (PRCA) following allogeneic haematopoietic stem cell transplantation (aHSCT) with major ABO incompatibility is responsible for transfusion dependent anaemia, impaired quality of life and iron overload. We conducted a retrospective study, over a 10‐year period, which included all consecutive patients who received a major ABO mismatched aHSCT, to assess the impact of specific treatment on PRCA. We did not observe any PRCA in the 57 aHSCT issued from cord blood. Among the remaining 631 patients, cumulative incidence of PRCA was 10·5% [range 8·2–13.0]. The median duration of resolved PRCA was 171 days [IQR 116; 261]. Pre‐transplant high isohaemagglutinins titre was associated with an increased risk of PRCA ( P < 10 −4 ). PRCA did not affect overall survival ( P = 0·95). Twenty‐two patients (33·3%) received at least one specific treatment. The most commonly used treatments were rituximab (17 patients) and donor lymphocyte infusion (DLI; seven patients). Regarding PRCA resolution, we did not observe a significant difference between treated or untreated subjects (HR = 0·93, 95% confidence interval (CI) 0·48– 1·80; P = 0·82). Similar results were observed with erythropoietin treatment (22 patients, HR = 0·86 95% CI: [0·47–1·57] P = 0·62). Our data do not support the use of erythropoietin, rituximab or DLI for the treatment of PRCA.